Isolation and Molecular Analysis of a Novel Neorickettsia Species That Causes Potomac Horse Fever - Omid Teymournejad (American Society for Microbiology, 2020)
ABSTRACT Potomac horse fever (PHF), a severe and frequently fatal febrile diarrheal disease, has been known to be caused only by Neorickettsia risticii, an endosymbiont of digenean trematodes. Here, we report the cell culture isolation of a new Neorickettsia species found in two locations in eastern Ontario, Canada, in 2016 and 2017 (in addition to 10 variable strains of N. risticii) from N. risticii PCR-negative horses with clinical signs of PHF. Gene sequences of 16S rRNA and the major surface antigen P51 of this new Neorickettsia species were distinct from those of all previously characterized N. risticii strains and Neorickettsia species, except for those from an uncharacterized Neorickettsia species culture isolate from a horse with PHF in northern Ohio in 1991. The new Neorickettsia species nonetheless had the characteristic intramolecular repeats within strain-specific antigen 3 (Ssa3), which were found in all sequenced Ssa3s of N. risticii strains. Experimental inoculation of two naive ponies with the new Neorickettsia species produced severe and subclinical PHF, respectively, and the bacteria were reisolated from both of them, fulfilling Koch’s postulates. Serological assay titers against the new Neorickettsia species were higher than those against N. risticii. Whole-genome sequence analysis of the new Neorickettsia species revealed unique features of this bacterium compared with N. risticii. We propose to classify this new bacterium as Neorickettsia finleia sp. nov. This finding will improve the laboratory diagnosis of and vaccine for PHF, environmental risk assessment of PHF, and understanding of PHF pathogenesis and Neorickettsia biology in general. IMPORTANCE Despite the detection of Neorickettsia species DNA sequences in various trematode species and their hosts, only three Neorickettsia species have been cell culture isolated and whole-genome sequenced and are known to infect mammals and/or cause disease. The molecular mechanisms that enable the obligatory intracellular bacterium Neorickettsia to colonize trematodes and to horizontally transmit from trematodes to mammals, as well as the virulence factors associated with specific mammalian hosts, are unknown. Potomac horse fever (PHF) is a severe and acute systemic infectious disease of horses, with clinical signs that include diarrhea. Neorickettsia risticii is the only known bacterial species that causes PHF. Ingestion of insects harboring N. risticii-infected trematodes by horses leads to PHF. Our discovery of a new Neorickettsia species that causes PHF and whole-genome sequence analysis of this bacterium will improve laboratory diagnosis and vaccine development for PHF and will contribute to our understanding of Neorickettsia ecology, pathogenesis, and biology.